ANALISIS PENGARUH KUALITAS PRODUK, ASOSIASI MERK, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMBELIAN (Study kasus pada Konsumen Sepeda Motor Scoopy di Semarang) - Dewi, Ayu Novita; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
In the span of a few months Honda Scoopy is still unable to compete with other matic product and lead to a decrease in sales. This study aimed to analyze the effect of product quality, brand associations and groups of reference on purchasing decisions Honda Scoopy motorcycle in Semarang.         The research sample of 100 people were taken from the population through non-probability sampling method with accidental sampling technique. The primary data research instrument was a questionnaire, which is then analyzed quantitatively.         Results of multiple linear regression analysis showed that the variable product quality, brand associations, and the reference group has a positive influence on purchase decisions. The variables that have the greatest influence is the quality of the product followed by the reference group and that has the least influence is the association of the brand. T test results showed that each independent variable has a significant influence on purchasing decisions. This equation model has a F value of 68.548 with a significance level of 0.000. Results of the analysis showed 67.2% coefficient of determination indicates that the variable product quality, brand associations, and the reference group only explain the influence on purchasing decisions, the rest is explained by other variables that are not described in this study.